Overall outage event of self-sustaining low-power cooperative relaying networks - Hoang-Sy Nguyen; Thanh-Khiet Bui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
This paper investigates the implementation of the household low-power energy harvesting (LoPEH) wireless sensor networks (WSN) over log-normal fading channels. The relays are battery-operated and the stochastic harvested energy flow to the batteries is characterized with the Markov property of energy buffer status. The communication is established with the combination of direct link and cooperative relays. The best relay is chosen based on a relay selection (RS) scheme namely optimal relay selection (OPRS). It can be drawn that within a particular range of signal-to-noise ratio (SNR), the energy harvesting (EH) relay-aided protocol can remarkably boost the overall system performance. On the other hand, the study reports how increasing the log-normal channel variance can degenerate the in-studied EH relaying protocol.